The Influence of Problem-Based Learning Model on the Improvement of Students' Critical Thinking Skills in IPAS Learning - Indah Wulandari; Aan Widiyono (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
Education plays an important role in shaping individuals to be critical, creative, and independent. However, the learning process in elementary schools is still dominated by conventional lecture methods that do not actively involve students, which affects their low critical thinking skills. This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model in improving the critical thinking skills of fourth-grade students at SD Negeri 2 Kuanyar, Jepara. The method used is a quantitative approach with a one-group pretest-posttest design, involving 19 students as the research sample. The research instruments were tested for validity and reliability using SPSS version 25. The analysis results show a significant increase between the pretest and posttest scores (t-count = 7.833 > t-table = 2.110; sig. = 0.000 < 0.05), which proves that the PBL model is effective in enhancing students' critical thinking skills. The implementation of PBL also encourages active participation, group discussions, as well as the ability to solve problems independently and collaboratively. Therefore, the PBL model is a feasible alternative learning strategy to improve the quality of education, particularly in developing critical thinking skills at the elementary school level.